2018
DOI: 10.1007/s10064-018-1333-3
|View full text |Cite
|
Sign up to set email alerts
|

Engineering geology of cinder gravel in Ethiopia: prospecting, testing and application to low-volume roads

Abstract: Expansion of the rural road network in Ethiopia requires the availability of low-cost materials for road construction, including capping layer and subgrade improvement, sub-base, base course, gravel wearing course and bituminised surface treatment. A reluctance to use cinder gravels for these purposes in the past has stemmed from the view that their properties, in terms of grading and CBR strength, are marginal and highly variable when compared to international specifications for road works. The geographical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
7
0
2
Order By: Relevance
“…It is also similarly used as a cement additive in the construction of reinforced concrete structures to improve the engineering properties of concrete [32][33][34]. Hossain and Hearn et al [32,35] reported that the blending of scoria as an additive material in concrete works proved efective in improving the strength, durability, and heat insulation properties of the concrete. Saltan and Ozen [36] in the experimental study on the usability of scoria as a subbase material reported the appropriateness of scoria as a partial replacement.…”
Section: Introductionmentioning
confidence: 99%
“…It is also similarly used as a cement additive in the construction of reinforced concrete structures to improve the engineering properties of concrete [32][33][34]. Hossain and Hearn et al [32,35] reported that the blending of scoria as an additive material in concrete works proved efective in improving the strength, durability, and heat insulation properties of the concrete. Saltan and Ozen [36] in the experimental study on the usability of scoria as a subbase material reported the appropriateness of scoria as a partial replacement.…”
Section: Introductionmentioning
confidence: 99%
“…Terefore, requirements for economical and more environmental-friendly cementing materials have extended interest in other cementing materials that can be used as alternatives to Portland cement which is available around constructing infrastructure. Historically, numerous kinds of volcanic scoria have been efectively utilized in dams and aqueducts, where the strength demand is not high but the durability and thermal cracking control are of major concern [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Scoria is a volcanic product that is abundantly available in various parts of the world such as; Turkey, Algeria, Papua New Guinea, Syria, Saudi Arabia, Cameroon, Indonesia, Rwanda, Tanzania, Yemen, Ethiopia, and many other subtropical countries [ 10 ]. In Ethiopia, Scoria gravel is extensively found especially in the Great Rift Valley, which crosses the northeastern part of the country including Akaki, Bishoftu, Mojo, Lake Ziway, Lake Chamo, Woliso, Butajira, Bekoji, Loggia, and Adama [ 11 , 12 ]. Because of its lightweight, rough circular surface, and high porosity, scoria gravel is vulnerable to compaction.…”
Section: Introductionmentioning
confidence: 99%